Literature Spaces problematizations in Uma Jornada Como Tantas, of Francisco Dantas and Essa Gente, of Chico Buarque - Pinto, Maria Gabriele Silva; Brito, Herasmo Braga de Oliveira (The ESPecialist, 2024)
The aim of this study is to discuss aspects of Brazilian neoregionalism in contemporary literature, problematize the literary space based on Brazilian neoregionalism, which emerges as a new trend in literature, and finally analyze how fictional and subjective spaces are configured and singularized in neoregionalist works: Uma Jornada como Tantas (2019) by Francisco Dantas and Essa Gente (2019) by Chico Buarque. The research is categorized as bibliographic and is based on the theoretical perspective of the following authors: Braga (2017), Bachelard (1993), Ozíres (2007), Brandão (2013), and Tuan (2015). First, the necessary foundation was sought to characterize how fictional and subjective spaces directly influence the characters’ identity formation, influencing their emotions, decisions, conflicts, and constitutions. Next, na attempt was made to understand how the characters’ subjectivities are directly linked to the space in which they are inserted. Finally, analyses of spaces in neoregionalist works were conducted, meticulously observing their composition in the characters’ identity formation, as well as how they act not only in the physical environment but also in the narrative construction, since the space is constructed through dialogues among the characters, their memories, experiences, and subjectivities, characterizing a certain place based on their experiences.